An Adaptive Approach to Discriminate the Persistence of Faults in Wireless Sensor Networks. (14th October 2012) - Mahapatro, Arunanshu; Khilar, Pabitra Mohan
Abstract : This paper presents a parametric fault detection algorithm which can discriminate the persistence (permanent, intermittent, and transient) of faults in wireless sensor networks. The main characteristics of these faults are the amount the fault appears. We adopt this state-holding time to discriminate transient from intermittent faults. Neighbor-coordination-based approach is adopted, where faulty sensor nodes are detected based on comparisons between neighboring nodes and dissemination of the decision made at each node. Simulation results demonstrate the robustness of the work at varying transient fault rate.